Design and Development of a Real-Time Delivery Tracking App Using WebSocket and Haversine - Bima Arya Kurniawan; Retno Mumpuni; Muhammad Muharrom Al Haromainy (bit-Tech, 2025)
The increasing demand for reliable real-time delivery tracking in furniture logistics highlights critical gaps in existing solutions: static geofencing without precise geodesic validation, polling-based protocols causing 1-3 second delays, and non-integrated Proof of Delivery (PoD) lacking automated location verification. These limitations result in inconsistent validation accuracy and limited transparency, directly impacting customer trust and operational costs. This research addresses these gaps by developing a novel tracking system uniquely integrating WebSocket-based bidirectional communication, Location-Based Services (LBS), and the Haversine Formula for geodesic distance validation, a combination not previously implemented for PoD-specific furniture logistics. The system comprises an Android driver application, Laravel-based backend with real-time WebSocket infrastructure, and monitoring interfaces for administrators and customers. Evaluation through 30 latency samples demonstrated stable WebSocket performance with average latency of 44.03 ms (SD=4.38ms; 95% CI=44.03±1.62ms), achieving 23-68 times faster transmission than traditional HTTP polling. Three geofence validation scenarios (50m, 100m, 200m radii) achieved 100% accuracy, with PoD triggering consistently restricted to authorized boundaries. Comprehensive functional testing confirmed reliable operational behavior across mobile and web modules. The practical impact includes automated location verification eliminating manual validation time, enhanced fleet visibility for large delivery trucks, and increased customer transparency through continuous tracking. These findings demonstrate that integrated WebSocket-Haversine-LBS architecture significantly improves delivery transparency, reduces validation errors, and enhances operational decision-making in furniture logistics. Future priorities include offline-first architecture, route optimization for heavy vehicles, and iOS platform support.